Peningkatan Kreativitas Anak Melalui Kegiatan Mewarnai di KB Tunas Bahari Pajagan Kecamatan Cisolok Kabupaten Sukabumi - Susilawati, Euis; Awal Maulana, Redi; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
The development of children's intelligence is greatly influenced by creativity-based education. Coloring skills are examples of creative potential that are no less important for the development of children's creativity, and this is done from an early age. This activity can increase children's creativity and improve their fine motor development. The purpose of this study is to increase children's creativity in coloring activities, this is because in the initial observation the level of creativity in coloring in KB Tunas Bahari Pajagan has not yet appeared. Children's creativity in coloring most of them do not know how to color the picture according to the original, cannot explain what is colored, or explain the meaning of the picture. They even tend to color images with just one color. Of the 15 students, there were no children who developed Very Well (BSB) or 0%, children who developed according to expectations (BSH) 13.3% with a total of 2 children, children who began to develop 33.3% with a total of 5 children, and children who were not yet developed (BB) as many as 53.4% with a total of 8 children. In this study, using the Classroom Action Research method in the implementation of observations, it was carried out using 2 cycles, in which 2 activities were carried out in each cycle. The results of this study show that free coloring activities can increase children's creativity in KB Tunas Bahari Pajagan, Cisolok District, Sukabumi Regency.